Contextual Meanings of Similarities in Âşık Veysel’s Poems - Ceren Selvi̇ (Akademik Dil ve Edebiyat Dergisi, 2026)
Analysis of the signs used in the language of poetry means bringing what the poet wants to say from the deep structure to the surface structure. Poetry is the art of bringing signs together accurately and artistically. What this means is that the desired emotion of the poem is conveyed by bringing the chosen language elements together harmoniously. These language elements which come together form the framework of the poetic language with the semantic bonds they create with each other. The concept of "context" determines how all the words that make up the poem will come together. The language used in poetry is a tool for the poet. While using language as a tool, the poet will want to convey their thoughts and feelings to the reader through context. However, it’s not possible for them to go out of context while doing this. The concept of word, which corresponds to a sign in language, cannot be separated from the context. Words must be in a consecutive order to form a meaningful text sequence because the signs in language are linear. When using language, sounds and words are placed one after the other. When the words connect to each other, a meaningful relationship will arise between them. As a result of this meaningful relationship, contextual meanings emerge. In this study, the contextual meanings of the metaphors identified in Âşık Veysel's poems are explained through tables. Before moving on to the review section, brief information and examples are given about the concepts of sign/referent/context.